Free volume vacancy behaviour and dynamic viscosity of diesel fuels with additives at elevated temperature and pressure: thermo-occupancy function - YAHŞİ, UĞUR (My University, 2022)
The reported pressure-volume-temperature (PVT) data of five different diesel fuels atT= 297.95-373.06 K andP= 0.1-457.2 MPa were described by the Simha-Somcynsky (SS) equation of state (eos). From the equilibrium condition imposed on the eos, the hole fraction,h=h(P,T), a form of free volume measure, was computed. Furthermore, our physically-based correlation implicating the thermo-occupancy function,Yh=Yh(h,T), in terms of a function ofh=h(P,T) andThas been extended in this study to estimate the dynamic viscosity,η, for the mixtures of commercially available fuels. The model bridges a direct relation from an equilibrium property,h, to the transport process,η, of the system and predicts the viscosity with the range from 0.15% to 0.31%. Newly designates \"viscoholibility\" function defined as the derivative of logarithm of viscosity with respect to hole fraction has been discussed. It has an exponential decaying behaviour with respect toh.
Keywords: Fizik; Genel Fizik; İstatistik fizik, termodinamik ve nonlineer dinamik sistemler; Temel Bilimler; Physics; General Physics; Statistical physics, thermodynamic and nonlinear dynamic systems; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; FİZİK, MATEMATİK; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; PHYSICS; MULTIDISCIPLINARY SCIENCES; PHYSICS, MATHEMATICAL; Multidisipliner; Matematiksel Fizik; Fizik Bilimleri; Multidisciplinary; Mathematical Physics; Physical Sciences; additives; diesel fuels; dynamic viscosity; Simha-Somcynsky; free volume; thermo-occupancy function; HOLE FRACTION; NEWTONIAN FLOW; DEPENDENCE; LIQUIDS; LINKING; PARAMETERS; MIXTURES; TERMS; STATE; PVT